Integration of Radio and Social Media as a Tool to Promote Visibility and Influence on Advertising Revenue - Appau, Grace Adiepena (UniMAC-GIJ, 2021)
This study focuses on how traditional media houses/platforms use social media to promote their brands and how that influences the allocation of advertising revenue by advertisers. In recent years, Ghanaians have embraced social media. This has driven traditional media to use the new media as a platform for real-time communication with various markets. A key advantage of social media in comparison to traditional alternatives is its mass reach and easy accessibility. Combining traditional and social media helps to build a wide audience share. Radio stations can use the extra engagement and direct relationship with their social media audience to help promote station and brand visibility Brand awareness has become an important variable that impacts customers’ perceptions of a brand (Karam et, al., 2015) Social media presence or visibility seems to be important to advertisers and corporate organizations when allocating advertising budgets in recent times. The notion is that social media “numbers” determine whether a particular station has a wide audience share or not. Despite the growth of social media, traditional media remains a formidable news creation and dissemination platform. Although a significant number of people consume news from social media, it is observed that such news traces its sources to traditional media outlets. Traditional media platforms, therefore, while they may be threatened by social media, remain an important source for validating the credibility of news items shared online. The association of such stories to credible traditional media platforms serves as a useful guarantee. In Ghana, corporate organizations and advertisers primarily rely on geo-poll ratings to determine which station has more audience. This process informs companies on how to distribute their advertising budgets and which stations should receive more budget. On the other hand, a radio station may have very good content but once it is not rated highly on geo poll, the station may struggle to raise revenue which usually comes from advertisement. It has been observed that corporate organizations now consider social media “metrics” as evidence of how visible a radio station is to the target market. The credibility of the Geopoll has been questioned by industry players as unscientific. The question, therefore, is, towards reevaluating audience share and visibility, how might social media presence or “metrics” be useful in allocation of advertising budget? This study seeks to examine the credibility of using social media presence as proof of radio visibility to the target market. In this research, Media Convergence theory and the Gratification Theory will be used as well as interviews, to investigate traditional radio (Onua FM, Okay FM, Accra FM, and Angel FM) use of social media as a tool for promoting visibility.
Thesis